INFLUENCE OF CROPPING SYSTEMS AND NUTRIENT MANAGEMENT ON NUTRIENT UPTAKE, PROTEIN CONTENT, YIELD, PRODUCTIVITY AND NET RETURNS OF PEARLMILLET (PENNISETUM GLAUCUM) - CHOUDHARY, R.S.; GAUTAM, R.C. (Annals of Agricultural Research, 2014)
Field experiment was conducted to study the effect of cropping systems and nutrient management in pearlmillet on nutrient uptake, quality, yield and net returns. Highest nutrient uptake and protein content were observed with combined application of 60 kg N/ha + 40 kg P2O5/ha + 10 t FYM/ha + biofertilizer. There were no significant influence observed on yield in both the years of experimentation whereas total productivity was found superior with pearlmillet-wheat system and highest net returns also. Among nutrient management practices yield and total productivity was found highest with 60 kg N/ha + 40 kg P2O5/ha + 10 t FYM/ha + biofertilizer while highest net return was obtained with 60 kg N/ha + 40 kg P2O5/ha + 5 t FYM/ha + biofertilizer.